Family Resilience in a Religious Pluralistic Society: A Social Construction Perspective - Nila Cantika Pangesti; Sudirman Sudirman; Supriyadi Supriyadi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Religious groups today often experience social conflict. However, this is not the case in the community of Ngadas Village, Poncokusumo Subdistrict, Malang Regency, which consists of Buddhists, Muslims, and Hindus. Family resilience becomes a challenge when family members adhere to different religions and live in a religiously pluralistic environment. The purpose of this study is to identify strategies for religiously pluralistic family resilience and analyze them using Peter L. Berger and Thomas Luckmann's social construction theory. This study employs an empirical research method with a sociological approach. Data were collected through interviews and documentation. The data were then processed in several stages: data examination, data classification, data verification, data analysis, and conclusion. The results of the study show that the resilience strategies of religiously pluralistic families include adaptation to the environment through active involvement in social and cultural activities, tolerance, the role of the family in shaping open-mindedness and empathy, and cultural traditions as the foundation of community life. Family resilience in religiously pluralistic communities is examined from a social construction perspective through three processes: First, the process of externalization, where the Ngadas village community creates the habit of living in harmony and respecting customs. Second, the process of objectification, where these habits are accepted as legitimate and binding social norms. Third, the process of internalization, where these values are embedded in each individual as part of their identity as Tengger people.